Notes on the genus nymphoides (menyanthaceae) of colombia (2005)
Nymphoides, a cosmopolitan genus, comprises to date 22 aquatic species. Two species are actually known to occur in Colombia, Nymphoides indica with a pantropical distribution and Nymphoides flaccida, an endemic species of the Colombian Llanos. Recently I got the opportunity to collect flowering and fruiting material of N. flaccida, which I take for presenting a broader description of the mentioned species. A key for the Colombian species is given. The geographical distribution, ecological preferences, and descriptions are presented under each species. Probably species richness of aquatic macrophytes in the neotropics, and particularly of Colombia, may be higher than presently recognized because of the incomplete knowledge of the aquatic flora.